EFEITOS DE FONTES DE BORO NO DESENVOLVIMENTO RADICULAR DO GIRASSOL (Helianthus annuus) EM RIZOTRONS - Castro, Paulo R. C.; Tavares, Silvio; Bertolotti, Luciana; Abe, Raphael G.; Yamada, Tsuioshi (REVISTA DE AGRICULTURA, 2016)
EFEITOS DE FONTES DE BORO NO DESENVOLVIMENTO RADICULAR DO GIRASSOL (Helianthus annuus) EM RIZOTRONS